2015
DOI: 10.5424/fs/2015243-07541
|View full text |Cite
|
Sign up to set email alerts
|

Soil compaction of various Central European forest soils caused by traffic of forestry machines with various chassis

Abstract: <p><em>Aim of study: </em>The primary objective of this paper was to compare the effects of different types of forestry machine chassis on the compaction of the top layers of soil and to define the soil moisture content level, at which machine traffic results in maximum compaction.</p><p><em>Area of study:</em> Measurements were conducted in eight forest stands located in Slovakia and the Czech Republic. The soil types in the stands subjected to the study were luvisols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 13 publications
(9 reference statements)
1
20
0
1
Order By: Relevance
“…An important factor differentiating soil changes after harvesting is the impact of different machinery. Allman et al [27] compared the influence of different logging machines on soil compaction and reported that all wheeled machines caused the same amount of soil compaction in the ruts, despite differences in tires, machine weight, etc. Cambi et al [28] studied the effect of bogie tracks on the physical properties of the soil during forwarding operations in a coniferous stand in northeastern Italy.…”
Section: Howmentioning
confidence: 99%
“…An important factor differentiating soil changes after harvesting is the impact of different machinery. Allman et al [27] compared the influence of different logging machines on soil compaction and reported that all wheeled machines caused the same amount of soil compaction in the ruts, despite differences in tires, machine weight, etc. Cambi et al [28] studied the effect of bogie tracks on the physical properties of the soil during forwarding operations in a coniferous stand in northeastern Italy.…”
Section: Howmentioning
confidence: 99%
“…Soil degradation is caused by many factors, including deforestation, infrastructure development, and construction, but inappropriate management of agricultural land is also a major cause (Terranova et al, 2009;Nunes et al, 2011). For example, increased mechanization and size of farm machinery has caused extensive soil compaction (a major factor in soil degradation) (Beylich et al, 2010;Allman et al, 2015); continuous tillage, which disrupts soil structure and increases soil organic matter loss, has accelerated rates of soil erosion in parts of the world (Martinez-Casasnovas and Ramos, 2009;Don et al, 2010;Crittenden et al, 2015); heavy grazing by livestock leaves land sparsely vegetated, compacted, and vulnerable to soil erosion (Lal, 1990;Nunes et al, 2011); and leaving cropland without a protective vegetative cover causes declines in soil organic matter content and leaves soil exposed to the erosive forces of wind and rain (Lal, 1990;Pimentel et al, 1995). Evidence is accumulating that intensive farming practices reduce the diversity and complexity of soil food webs (Tsiafouli et al, 2016), which has consequences for the functioning of soil and its ability to buffer against extreme weather events (De Vries et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The density increase recorded for the mechanized CTL treatment was significantly higher than for the manual CTL treatment. As soil compaction is highly complex and a very recent research topic [46][47][48][49][50], further analysis should be conducted if this indicator is of crucial importance.…”
Section: Discussionmentioning
confidence: 99%